2015
DOI: 10.1016/j.aoas.2015.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Production of amylases from Bacillus amyloliquefaciens under submerged fermentation using some agro-industrial by-products

Abstract: Thirty-one bacterial isolates out of 133 isolates, were obtained from rhizosphere of Egyptian clover plants, and had variant capability for starch degradation on starch agar medium. The isolate E109 was the most potent being 72.5 U ml À1 and 2.5 for amylase activity and starch hydrolysis ratio (SHR), respectively, at 50°C. The potent isolate E109 was identified based on phenotypic characteristics, phylogenetic positions based on 16S rRNA gene analysis and base sequences (submitted to NCBI Gen Bank). 16S rRNA g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
1
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(85 citation statements)
references
References 31 publications
3
67
1
6
Order By: Relevance
“…The current investigation strongly agreed with the findings of Dash et al [13] who demonstrated significant amylase yield from Bacillus sp. at the end of 24 h. Conversely, Abd-Elhalem et al [5] demonstrated the maximum yield of amylase from Bacillus sp. during 36 h of incubation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current investigation strongly agreed with the findings of Dash et al [13] who demonstrated significant amylase yield from Bacillus sp. at the end of 24 h. Conversely, Abd-Elhalem et al [5] demonstrated the maximum yield of amylase from Bacillus sp. during 36 h of incubation.…”
Section: Discussionmentioning
confidence: 99%
“…Our results totally agree with the findings of Samanta et al [12] and Karatas et al [13] who demonstrated maximum amylase production in the presence of starch. On the other hand, Deb et al [14] and Abd-Elhalem et al [5] had recorded maximum amylase production from Bacillus sp. in the presence of corn flour and different agro-industrial wastes respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this result, wheat bran was selected for the production of the enzyme and to perform the subsequent Agroindustrial by-products have been evaluated as substrates for the production of amylase in order to reduce production costs through fermentation in solid state and submerged fermentation. Abd-Elhalem et al 27 used industrial waste in the production of the amylase enzyme by Bacillus amyloliquefaciens in submerged fermentation, and the residue from potato processing exhibited higher activity (80.1 U mL -1 ) than soluble starch (72.3 U mL -1 ). Amylase production from Bacillus cereus MTCC 1305 by solid state fermentation using wheat bran resulted in a greater production of this enzyme (94 U g -1 ) than by production with rice flakes (34 U g -1 )…”
Section: Resultsmentioning
confidence: 99%
“…Recently, few investigations had already reported the overwhelming yield of amylases from distinct bacterial sources using unique organic wastes viz. cassava bagasse (Ray and Kar 2009), cow dung (Vijayaraghavan et al 2015), potato starchy wastes (Abd-Elhalem et al 2015), and organic chicken wastes (Hasan et al 2017). But study on the utilization of goat dung as feedstock for the successful production of amylase is not evidenced so far.…”
Section: Discussionmentioning
confidence: 99%